2013
DOI: 10.1002/we.1601
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of airflow through a Savonius rotor

Abstract: The aim of this report is to present a model of a rigid-rotor system based on computational fluid dynamics (CFD), which is applied on a vertical axis wind turbine (VAWT) research. Its originality results from the use of the average value of the variable rotational speed method taken in a periodic steady-state (PSS) of the VAWT rotor instead of the classical fixed rotational speed method. This approach was chosen in order to determine the mechanical and aerodynamic parameters of the wind turbine. The modeling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…This numerical model takes advantage of resolving the angular velocity of the rotor as a time-varying variable, according to the unsteady aerodynamics of the Savonius rotor. This is a key point since performing unsteady simulations by means of coupling fluid-flow equations with the rigid-body ones allows to achieve a proper and reliable reconstruction of the dynamic behaviour of the Savonius wind rotor [19]. The same computational model has been also applied to investigate a more complex flow field, such as the case of a Savonius rotor with conventional semi-cylindrical blades, provided with an innovative conveyor-deflector curtain system, selforienting relative to the wind direction.…”
Section: Introductionmentioning
confidence: 99%
“…This numerical model takes advantage of resolving the angular velocity of the rotor as a time-varying variable, according to the unsteady aerodynamics of the Savonius rotor. This is a key point since performing unsteady simulations by means of coupling fluid-flow equations with the rigid-body ones allows to achieve a proper and reliable reconstruction of the dynamic behaviour of the Savonius wind rotor [19]. The same computational model has been also applied to investigate a more complex flow field, such as the case of a Savonius rotor with conventional semi-cylindrical blades, provided with an innovative conveyor-deflector curtain system, selforienting relative to the wind direction.…”
Section: Introductionmentioning
confidence: 99%
“…Zanon et al [15] solved potential flow equations in conjunction with integral boundary layer equations formulated for VAWT rotors, using a semi-inverse iterative algorithm. From their simulations, they inferred that VAWTs can be designed to avoid the occurrence of dynamic stall resulting from blade-vortex interaction in the downward part of rotor rotation during gusts and normal operation, and even at low tip-speed ratios [16]. Scheurich et al [14] implemented a CFD scheme based on the vortex transport model (VTM).…”
Section: Introductionmentioning
confidence: 99%
“…The governing momentum equation is expressed in terms of the vorticity and velocity and is the result of finding the curl of the velocity and pressure-based N-S momentum equation. In their work on the steady-state and dynamic simulations of Savonius rotors, Jaohindy et al [16] found that the best approximations of the static torque coefficient, the dynamic torque coefficient and the power coefficient were obtained using the shear stress transport-k-ω model rather than the k-ε turbulence model. At startup, dynamic torque coefficient curves of a Savonius rotor oscillate around fixed values in polar coordinates [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical steps of Savonius wind turbine simulation in 1-DOF DBFI method are applied by using polyhedral mesh [7]. In the research, 2 blades straight Savonius is simulated in STAR CCM+ program.…”
Section: Introductionmentioning
confidence: 99%